1999
DOI: 10.1046/j.1439-037x.1999.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Water Content and Growth of Seed and Fibre of Three Cotton Genotypes

Abstract: Three cotton genotypes "varying in their _nal seed size#\ viz[ H!5 and H!3 "Gossypium hirsutum L[# and V!686 "Gossypium herbaceum L[# were studied for their growth kinetics of seed and _bre[ Both biphasic linear and poly! nomial models were used to demark di}erent phases of cotton seed growth[ The polynomial model appeared to be appropriate to de_ne the growth phases of cotton seed as compared to the linear model[ The rate and the duration of dry matter accumulation were obtained by di}erentiating the best!_t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The findings also support the hypothesis that higher rate of water uptake is required for elongation growth and higher levels of water content supports higher rate of dry matter accumulation (Rabadia et al 1999). …”
Section: From Above Points It Was Concluded That Cotton Fiber Developsupporting
confidence: 83%
“…The findings also support the hypothesis that higher rate of water uptake is required for elongation growth and higher levels of water content supports higher rate of dry matter accumulation (Rabadia et al 1999). …”
Section: From Above Points It Was Concluded That Cotton Fiber Developsupporting
confidence: 83%
“…Vertical bars represent ± SD, or SD are within the symbols. correlation between cell elongation and water content (P ≤ 0.001) is well documented (Cosgrove 1993, Rabadia et al 1999.…”
Section: Resultsmentioning
confidence: 75%
“…Since the fresh weight and dry weights showed close correlation, the water content also showed significant relationship (P< 0.01). A number of the studies have shown that water content plays an important role in increase in the size of cotton fiber (Gokani and Thaker, 2001), cotton seed (Rabadia et al, 1999) and internodes development (Patel and Thaker, 2007). Leaf area in the first stage 20 mm 2 and then gradually increased with different leaf up to 3000 mm 2 .…”
Section: Resultsmentioning
confidence: 99%